THE EFFECT OF GIVING BONUSES ON INCREASING SALESMEN'S WORK IN INCREASING MOTORCYCLE SALES - Melisa Kurnia Asfitri; Tsurayya Syarif Zain; Heni Yuvita; Raras Risia Yogasnumurti (SEAN Institute, 2023)
This study aims to see how much influence and contribution incentives have on improving the performance of motorcycle sales. The research sample used was 30 respondents, and the research method used used a quantitative approach, the data analysis technique in this study used validity, reliability, simple linear regression and hypothesis testing using the coefficient of determination test. The results of the study concluded that there was a positive and significant influence between giving bonuses on sales performance with a constant value of 3.467 or a bonus coefficient value of 0.167. the results of the hypothesis test obtained that the effect of giving bonuses contributed 21.1%, and 78.9% was influenced by other salary and benefit factors.